2022
DOI: 10.1186/s12909-021-03058-z
|View full text |Cite
|
Sign up to set email alerts
|

A focus on the future of opioid prescribing: implementation of a virtual opioid and pain management module for medical students

Abstract: Background The United States opioid epidemic is a devastating public health crisis fueled in part by physician prescribing. While the next generation of prescribers is crucial to the trajectory of the epidemic, medical school curricula designated to prepare students for opioid prescribing (OP) and pain management is often underdeveloped. In response to this deficit, we aimed to investigate the impact of an online opioid and pain management (OPM) educational intervention on fourth-year medical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The students interrogated felt limited competence regarding the therapeutic use of opioids and MC. Several other studies also came to the conclusion that medical students feel insufficiently prepared to deal with opioids [ 28 , 29 ] or MC [ 16 , 17 , 30 , 31 ]. We showed that the seminar mostly helped improve the students’ perceived competence in dealing with a therapy involving MC, but also in dealing with patients with somatoform or chronic pain disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The students interrogated felt limited competence regarding the therapeutic use of opioids and MC. Several other studies also came to the conclusion that medical students feel insufficiently prepared to deal with opioids [ 28 , 29 ] or MC [ 16 , 17 , 30 , 31 ]. We showed that the seminar mostly helped improve the students’ perceived competence in dealing with a therapy involving MC, but also in dealing with patients with somatoform or chronic pain disorders.…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition, developing further training/educational tools to address the unmet needs in pain practice stands as an educational obligation. 22,23 Since its foundation in 1934, the Italian Society of Anaesthesia, Analgesia, Resuscitation, and Intensive Care (Società Italiana di Anestesia, Analgesia, Rianimazione e Terapia Intensiva, SIAARTI) has been devoted to promote the scientific and cultural development in multiple anesthesia-related fields, including pain medicine, by issuing guidelines on pain management. [24][25][26][27] Furthermore, in the last few years, SIAARTI promoted initiatives aimed at bridging the gaps in pain medicine in the Italian scenario which highlighted relevant educational needs to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Second, education is a relevant component of therapeutic management as education alone was able to change appropriate analgesic use when motivated by the possibility to earn continuing medical education (CME) credits 21 . In addition, developing further training/educational tools to address the unmet needs in pain practice stands as an educational obligation 22,23 …”
Section: Introductionmentioning
confidence: 99%
“…While many integrate interactive online features to engage participants in active learning, there are three main areas which are lacking in current available modules. Firstly, many modules lack clear curriculum, 3,4 perhaps due to the complexity of opioid management. Secondly, real-time input which has been recommended for effective online learning 5 is mostly unavailable.…”
Section: Introductionmentioning
confidence: 99%